Scheduling continuous aluminium casting lines - ALKAYA, ALİ FUAT (TAYLOR & FRANCIS LTD, 2008)
This study considers the problem of scheduling casting lines of an aluminium casting and processing plant. In aluminium processing plants, continuous casting lines are the bottleneck resources, i.e. factory throughput is limited by the amount of aluminium that can be cast. The throughput of a casting line might be increased by minimizing total setup time between jobs. The objective is to minimize setup time on production lines for a given time period while balancing workload between production lines to accommodate potential new orders. A mathematical formulation for scheduling jobs to minimize the total setup time while achieving workload balance between the production lines is presented. Since the casting scheduling problem is an NP-hard problem, even with only one casting line, a four-step algorithm to find good solutions in a reasonable amount of time is proposed. In this process, a set of asymmetric travelling salesman problems is followed by a pairwise exchange heuristic. The proposed procedure is applied to a case study using real casting data.
Keywords: aluminium cast scheduling; asymmetric travelling salesman problem; heuristics; PARALLEL MACHINES; STEEL PRODUCTION; OPTIMIZATION; ALGORITHMS; COLONY